Prevalence of Osteoporosis and Osteopenia in Iraqi Premenopausal and Postmenopausal Subjects among a Sample of Patients Attending Baghdad Teaching Hospital - Ali Hussein Al-Hafidh (Journal of Global Pharma Technology, 2018)
Back ground: Osteoporosis is a major public health problem and more common in women and older people Objective: to determine the prevalence of osteoporosis and osteopenia in premenopausal and postmenopausal subjects attending Baghdad teaching hospital  Methods: A cross sectional study was carried out for a period of one year in Baghdad teaching hospital Results:   A total of 240 subjects were included in this study, they were divided into 2 groups: the first group included 120 postmenopausal women with a mean age (59.93±6.88) and the second group included 120 premenopausal women with a mean age (46.36±4.07).Significant differences of bone mineral density of lumbar spine and both femurs between postmenopausal and premenopausal subjects. The percentage of osteoporosis and osteopenia in premenopausal was (26.7%) and (3.3%) respectively and in postmenopausal subjects was (34.17%) and (52.5%).T-score was used for postmenopausal subjects and Z-score for premenopausal subjects. The percentage of osteoporosis and osteopenia was higher in lumbar spine in both postmenopausal and premenopausal subjects than femurs. Normal BMD of right femur was higher than left femur in both postmenopausal and premenopausal subjects. Conclusion: The prevalence of osteoporosis and osteopenia in premenopausal was (26.7%) and (3.3%) and in postmenopausal subjects was (34.17%) and (52.5%) respectively. The percentage of osteoporosis and osteopenia was higher in lumbar spine in both postmenopausal and premenopausal subjects than femurs. Recommendations: Essential measures are needed for public education particularly dietary habit, lifestyle modification and widespread distribution of information about osteoporosis and its prevention.Keywords: Osteoporosis, Osteopenia, Postmenopausal, Premenopausal.